Prevalence of thyroid nodules and characteristics of thyroid ultrasound in children with goiter: a single center experience - Fahad Al Juraibah; Khalid Al Noaim; Abdulaziz AlDbas; Ahmed AlMuallimi; Omar AlOtaibi; Mozon AlShareef; Alanoud AlSuhibani; Ahmed AlZaharani; Mohammed AlDubayee; Amir Babiker (BMC, 2022)
Abstract Background Goiter is a common presenting sign of various thyroid diseases in children. Thyroid nodules are clinically and/or radiologically significant findings due to their high malignancy rate. The ultrasound (US) characteristics of pediatric patients with goiter are rarely reported in literature; thus, the purpose of this study is to assess the characteristics of thyroid US and the prevalence of thyroid nodules in pediatric patients with goiter. Methods A retrospective review of children and adolescents under the age of 18 (2015-2020) referred for neck ultrasound due to goiter in clinical examination. Results A total of 262 patients were included with a mean age of 13.77 ± 3.7 years. Thyroid antibodies were positive in 119/262 (45.4%) patients. Thyroid US reported to be abnormal in 210/262 (80%) patients. Thyroid nodule were found in 33.6% (n = 88/262) of patients with goiter and in 41.9% (n = 88/210) of patients with abnormal thyroid US result. Patients with positive antibodies had more of heterogeneity and hypervascularity of the gland on thyroid US (P < 0.001). On the other hand, thyroid nodules were more likely to be presented in patients with negative thyroid antibodies (P = 0.025). The heterogeneity within the thyroid positive group was significantly correlated with increasing TPOAb (P < 0.001) and TSH levels (P < 0.028). Heterogeneity on US had a positive predictive value (P = 0.041), while hypervascularity had low prediction for thyroid nodules (P = 0.022). Age, gender, family history of thyroid diseases, antibodies status and echogenicity in US did not show any significant associations with thyroid nodules. Papillary thyroid carcinoma was diagnosed in six patients and one of these patients was positive for thyroid antibodies. Conclusion Thyroid nodules are quite common in our population. Thyroid nodules were significantly associated with heterogeneity in US. Although, no clinical or biochemical factors could predict the presence of thyroid nodules on thyroid US in our cohort, the absence of thyroid antibodies should lower the threshold for performing thyroid US.